A Genealogy of Law: Inherent Sovereignty and First Nations Self-Government - Borrows, John J. (Osgoode Hall Law Journal, 1992)
First Nations self-government in Canada has often been regarded as extinguished or delegated from the British Crown or the Canadian federal government. First Nations self-government among the Chippewas of the Nawash Band in southern Ontario has not been extinguished or delegated, but continues to exist as an inherent exercise of community sovereignty. The idea of existing Aboriginal self-government in modern-day Ontario contrasts with many prevailing notions about Native society in Canada today. The inherent and unextinguished nature of self-government among the Nawash Band is demonstrated by examining the events of the author's ancestors and community in their interactions with foreign settlers. The investigation of this history is undertaken from a Native perspective to access and establish an alternative vision of the political and legal status of First Nations self-government. The particular interactions between Native and non-Native societies that establish a continuing, inherent exercise of sovereignty are: the War of 1812; the acceptance of Christianity; the preservation of traditional Native health care, education and language; the entering into of treaties; and the maintenance of self-government under the federal Indian Act through the exercise of statecraft and economic development. The author argues that recounting these interactive experiences from a Native perspective can infuse legal and political discourse with different alternatives and can grant to First Nations people the liberty that they desire to continue to pursue their aspirations according to their collective goals.